Oil-gas two-phase seepage model in fractured carbonate reservoirs - Xia, Boyi (Frontiers in Energy Research, 2022)
Fractures are developed in fractured carbonate reservoirs. Traditional fracture characterization methods and seepage mathematical models cannot accurately describe the complex spatial distribution of large-scale fractures and their stress sensitivity, and do not consider the two-phase seepage of oil and gas, resulting in the dynamic analysis results have large errors. Aiming at this problem, a two-phase seepage model of oil and gas in fractured carbonate reservoirs considering stress sensitivity is established in this paper, and the semi-analytical solution of the model is obtained by using three-dimensional source function theory and finite difference method. The accuracy of the model is verified by comparison with commercial numerical simulation software, the production performance curve of oil and gas two-phase is drawn, and the influence of key seepage parameters of reservoirs and fractures on production performance is analyzed. The results show that the hybrid solution method of 3D source function and finite difference can realize the accurate and efficient solution of 3D discrete fracture oil and gas two-phase seepage model. The stress sensitivity effect leads to serious loss of fracture permeability and increase of fluid seepage resistance, which seriously affects the production of oil wells. The greater the fracture permeability, the higher the initial value of production, and the higher the position of the production curve. The longer fracture length, the higher the production curve in the early and middle production stages, and the slower the production decline.